Sistem Aplikasi Buku Tamu Berbasis Web di Dinas Tenaga Kerja dan Transmigrasi - Aenul Hayat; Sofiansyah Fadli (Lembaga Pengembangan Kinerja Dosen, 2023)
Along with the rapid advancement of information technology in various aspects of life in utilizing technological advances, especially at the Kantor Dinas Tenaga Kerja Dan Trasmigrasi village office as in the reception of guests is still done manually and it takes a web-based application.The purpose of the website at Kantor Dinas Tenaga Kerja Dan Trasmigrasi Village is to produce dynamic performance and be easy to update at any time, besides that this website can also be a means for Kantor Dinas Tenaga Kerja Dan Trasmigrasi Village. to provide alternative media that are easier to learn for the community..